AGAMA TANPA NAMA: KEHADIRAN, POLITIK, DAN IDENTITAS AGAMA MERATUS LOKAL DI DEPAN NEGARA DAN MEDIA (PENELITIAN PENDAHULUAN): Array - Supriansyah Supriansyah (Jurnal Kearsipan, 2020)
This article discusses the existence and framing of Meratus local religion in various media in the form of writings and videos, such as State regulations or documents, mass media news, research, and books that have searched and written down Meratus local religion. This article examines the problem above by focusing on two important questions. First, how is the representation and existence of religion before the media and the administration and politics of the State? Second, how is the struggle of the Dayak Meratus community to the process of marginalization in an effort to gain recognition from the State, especially after the decision of the Constitutional Court (Mahkamah Konstitusi) in 2017? By exploring various opinions and visual images that are less sympathetic to the Meratus local religion which is spread in various media above, the position of Dayak Meratus local religion is still marginalized, making the Dayak Meratus still have to submit to parties in framing and constructing what they believe and embrace until now. This condition makes the local religion of Dayak Meratus increasingly eroded and always disappears before the State and official religion until now, since their religion is not compatible with the politics of order and development.